Revitalization of Regional Language as Cultural Identity in the Digital Era - Ida Bagus Rai Putra; Desak Nyoman Alit Sudiarthi; Ni Putu N. Widarsini; I Wayan Teguh; I Ketut Nama; I Gede Bagus Wisnu Bayu Temaja (Eastasouth Institute, 2025)
Local languages represent a vital pillar of cultural identity, yet they currently face serious challenges due to globalization, urbanization, and the dominance of national and foreign languages. This study aims to analyze strategies for revitalizing local languages in the digital era as an effort to preserve their existence and strengthen Indonesia’s cultural identity. The research employs a qualitative descriptive method with data collected through literature review, digital content analysis, and examination of revitalization practices conducted by communities, educational institutions, and government agencies. The findings indicate that digital technology, particularly social media, language learning applications, and creative platforms, offers significant opportunities for sustaining local languages. Revitalization efforts, however, require not only technological innovation but also multi-stakeholder collaboration among policymakers, academics, and communities. The study concludes that local languages hold great potential to thrive within digital spaces, thereby reinforcing cultural identity among younger generations amidst global cultural homogenization.